Combining body mass index and waist height ratio to assess the relationship between obesity and serum uric acid levels in adolescents - Liu, Shan; Wei, Wei; Cheng, Yuan; Chen, Jing-Yi; Liu, Yang; Wu, Zhi-Ping; Hu, Meng-Die; Zhao, Heng; Li, Xiao-Feng; Chen, Xin (Frontiers in Pediatrics, 2023)
Background: The study aims to explore the relationship between obesity and serum uric acid in adolescents by combining body mass index and waist height ratio. Methods: 475 adolescents in our study were classified as normal weight without central obesity (NW), normal weight but central obesity (NWCO), overweight or obesity without central obesity (OB) and overweight or obesity with central obesity (OBCO). Odds ratios (OR) and 95% confidence intervals (CI) for hyperuricemia were calculated using a logistic regression model. The dose-response association between obesity indicators and serum uric acid were explored by restricted cubic spline model. Results: The highest serum uric acid level and the OR for hyperuricemia were found in the OBCO group, regardless of sex. After controlling for waist height ratio, the risk of hyperuricemia increased with increasing body mass index in boys and girls. The restricted cubic spline model showed that boys had higher ORs for hyperuricemia at the 25th and 75th percentiles of body mass index than for waist height ratio and girls had a higher OR for hyperuricemia than waist height ratio at the 25th percentile of body mass index. Conclusions: Hyperuricemia in adolescence was not only associated with the overweight or obesity in BMI, but with the combination of overweight or obesity in BMI and central obesity in WHtR. However, in boys and girls, the increased risk of hyperuricemia associated with elevated body mass index was significantly better than that of waist height ratio.